Pengaruh Media Video Sinematik terhadap Kemampuan Berpikir Kritis Siswa - Sidiq, Angga Permana; Jayadinata, Asep Kurnia; Iswara, Prana Dwija (Jurnal Pena Ilmiah, 2019)
This research is based on the critical thinking skills of elementary school students. The goal of this research is to find out how the influence of cinematic video media towards students' critical thinking; to find out the different influence of cinematic video media and conventional learning on students' critical thinking skills; and to find out how the students’ respond to learning using cinematic video media. The design of this research is quasi-experimental with a nonequivalent control group design. The population of this research is the class V elementary school students in Cisarua Subdistrict with a research sample of SDN Ciuyah II class V as the experimental class and SDN Cisalak II class V as the control class. The instruments used in this research are thinking ability test questions, teacher observation sheets and student activities, attitude scale questionnaires, and interviews. Based on the results of the research, it can be concluded that: There is a positive influence that shows an increase in the ability of students in the experimental class, the use of better video media on how to improve students' thinking skills, and most students in the experimental class respond positively to learning using cinematic video media.